2005
DOI: 10.1124/dmd.104.003244
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Uptake of the Novel Antifungal Agent Caspofungin

Abstract: ABSTRACT:Caspofungin (CANCIDAS, a registered trademark of Merck & Co., Inc.) is a novel echinocandin antifungal agent used in the treatment of esophageal and invasive candidiases, invasive aspergillosis, and neutropenia. Available data suggest that the liver is a key organ responsible for caspofungin elimination in rodents and humans. Caspofungin is primarily eliminated by metabolic transformation; however, the rate of metabolism is slow. Accordingly, it was hypothesized that drug uptake transporters expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 18 publications
4
52
1
Order By: Relevance
“…Nevertheless, very little is known regarding the possible role of transporters in hepatobiliary elimination of micafungin in rats (Abe et al, 2008b), and no information is available in humans. In contrast, for another echinocandin, caspofungin, the active transport mechanisms possibly mediating its hepatic uptake have been investigated in experiments that used HeLa cells heterologously expressing the hepatic OATP isoforms (Sandhu et al, 2005). These uptake transporters have been suggested to play key roles in the hepatic elimination of caspofungin.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, very little is known regarding the possible role of transporters in hepatobiliary elimination of micafungin in rats (Abe et al, 2008b), and no information is available in humans. In contrast, for another echinocandin, caspofungin, the active transport mechanisms possibly mediating its hepatic uptake have been investigated in experiments that used HeLa cells heterologously expressing the hepatic OATP isoforms (Sandhu et al, 2005). These uptake transporters have been suggested to play key roles in the hepatic elimination of caspofungin.…”
Section: Discussionmentioning
confidence: 99%
“…No inhibition of P-gp 96 Substrate and inhibitor of OAT1B1. 96 CYP3A4 inhibition by caspofungin causes a 76% decrease in the metabolism of cytarabine.…”
Section: Caspofunginmentioning
confidence: 99%
“…96 CYP3A4 inhibition by caspofungin causes a 76% decrease in the metabolism of cytarabine. 187 CYP inducers (e.g., rifampin, nevirapine, efavirenz, carbamazepine, dexamethasome and phenytoin) induce the metabolism of caspofungin.…”
Section: Caspofunginmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from a clinical study conducted by Stone et al (2004) suggested that RIF both induced and inhibited the disposition of caspofungin, which has been shown to be a substrate of OATP1B1 (Sandhu et al, 2005). In another clinical study, when RIF and repaglinide were coadministered, RIF acted as an inducer and inhibitor of repaglinide metabolism (Bidstrup et al, 2004).…”
mentioning
confidence: 99%